FORMULATION AND CHARACTERIZATION OF DILTIAZEM TRANSDERMAL SYSTEM FOR THE TREATMENT OF HYPERTENSION - Shukla, Rama; Omray, L. K. (International Journal of Current Pharmaceutical Research, 2016)
Present study deals with the formulation and characterization of matrix type transdermal drug delivery system (TDS) of diltiazem hydrochloride for the treatment of hypertension. The TDS was prepared by the solvent evaporation method on a mercury substrate. Ten formulations were prepared which differed in the ratio of matrix forming polymers. Formulations TDS1 to TDS10 were composed of HPMC (hydroxypropyl methylcellulose), PVA (polyvinyl alcohol) and gelatin 10%, w/v in the combination of single polymer, two polymer (1:1) and three polymer in the ratio of 1:1:1, 1:2:1, 2:1:1 and 1:1:2 respectively. All the ten formulations contained 5 % (w/w) of diltiazem hydrochloride, 1 % (v/w) of propylene glycol and 1 % (w/w) of tween 80 (based on total polymer weight). The transdermal drug delivery system characterized for various physicochemical properties such as thickness, moisture content (MC), moisture uptake, water vapor transmission (WVT), folding endurance, drug excipients interaction, drug content and in vitro release study. On the basis physicochemical properties and in vitro release study, formulation TDS8 was found to be better than the other formulations and it was selected as the developed formulation.